Developing ESP Supplementary Book Based on Project Based Learning Model For Mechanical Engineering Students - Yuliana Firmanda; Widiarini Widiarini; Siti Rofi’ah; Istina Atul Makrifah (Journal of Development Research, 2021)
This paper aims to develop ESP Supplementary book for mechanical engineering students in high level education. This is a Borg & Gall Research and Development (R&D) by using questionnaire and unstructured interview instrument. The research subject is 20 fourth semester students of mechanical engineering major in UNU Blitar. The limitation of this study is developing ESP supplementary book based PBL with engineering materials as the topic of the book. The process development of Engineering Materials Supplementary Book Based on ESP and PBL consists of some steps those are (1) Need analysis; (2) Product arrangement; (3) Product testing; and (4) Product revision if it is necessary. This research finds that the supplementary book is valid in three aspects of media (77.5%), content (83.3%) and language (83.3%) and feasible to use as supplement material for the mechanical engineering students. Based on the satisfaction questionnaire this product is appropriate for the mechanical engineering students to learn about English for Specific Purposes in form of Project Based Learning model implementation in percentage about 80% agree and 15% very agree.